Investigation of Transcranial Direct Current Stimulation Combined with Conventional Speech Rehabilitation Therapy to Cure Non Fluent Aphasia after Stroke - Hong ZHANG; Jing LIU; Weifeng YANG; Qian TANG (康复学报)
Objective:To explore the clinical curative effect of the transcranial direct current stimulation (tDCS) combined with conventional speech rehabilitation therapy on non fluent aphasia after stroke, and to provide the basis of tDCS for its application in speech rehabilitation after stroke.Methods:Thirty-six cases of patients in recovery stage with aphasia after stroke were randomly divided into treatment group (n=18) which treated with the tDCS of left and right inferior frontal gyrus triangle area also stimulates respectively with conventional speech therapy, and control group (n=18) which treated with the tDCS false stimulation along with conventional language training. Both groups were treated five weeks, and the spontaneous speech, listen to understand, recall, named performance changes were observed and valued by western aphasia battery (WAB).Results:Both groups were improved significantly in spontaneous speech, retelling, performance after treatment (P<0.05). And the outcome of the treatment group was better than the control group (P<0.05).Conclusion:The positive tDCS stimulus on left inferior frontal gyrus triangle area, and the negative tDCS stimulus on right inferior frontal gyrus triangle area combinded with the conventional language treatment could improve the performance of non fluent aphasia after stroke in spontaneous speech, repetition and named performance.